Effect of Temperature Fluctuation, Substrate Concentration, and Composition of Starchy Substrates in Mixture and Use of Plant Oils as Antifoams on Biogas Production - Tumutegyereize, Peter; Ketlogetswe, Clever; Gandure, Jerekias; Banadda, Noble (Environmental Progress & Sustainable Energy, 2019)
This work investigated the effect of temperature fluctuations, substrate concentration and composition on foaming in anaerobic co-digestion of matooke, cassava, and sweet potato peels for biogas production as well as the use of plant oils as antifoams. In general, obtained results show that temperature fluctuations from mesophilic (≥25 C) to psychrophilic range (<25 C) is the major factor behind foaming in anaerobic digestion. Specifically, at concentrations of 6 and 9 g VS/L with methane yield of 1228.69 and 735.55 Nml CH4/g VS, respectively, for 2:0:1 ratio, there was no foaming until after 7.6 days compared with the other ratios where foaming generally started after 3.5 days. This indicated that, apart from high substrate concentration, foaming is also a function of substrate composition. Plant oils were found to suppress foaming only if temperatures were above 25 C, indicating temperature fluctuations to be the main factor in foaming even in the presence of antifoams.
Keywords: Temperature fluctuation; Biogas production; Foaming; Antifoams; Substrate concentration